2022
DOI: 10.1161/jaha.122.026294
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Prognostic Significance of Malnutrition in Older Japanese Adults at High Surgical Risk Undergoing Transcatheter Aortic Valve Implantation

Abstract: Background The usefulness of preprocedural nutritional status to stratify prognosis after transcatheter aortic valve implantation has been evaluated; however, the studies conducted so far have been relatively small and/or focused on a single nutritional index. This study sought to assess the prevalence and prognostic impact of malnutrition in patients with severe aortic stenosis undergoing transcatheter aortic valve implantation. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…These are different geriatric syndromes but inextricably intertwined. It did not go unnoticed that Ishizu et al 2 reported a higher prevalence of moderate/severe malnutrition regardless of index used in patients who are frail in comparison with patients who are not frail (statistically significant differences) as measured by the Clinical Frailty Scale. Looking closely at their Table 2 and the intersection between GNRI and Clinical Frailty Scale reported by Ishizu et al, 2 the overlap between frailty and moderate/severe malnutrition is evident.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…These are different geriatric syndromes but inextricably intertwined. It did not go unnoticed that Ishizu et al 2 reported a higher prevalence of moderate/severe malnutrition regardless of index used in patients who are frail in comparison with patients who are not frail (statistically significant differences) as measured by the Clinical Frailty Scale. Looking closely at their Table 2 and the intersection between GNRI and Clinical Frailty Scale reported by Ishizu et al, 2 the overlap between frailty and moderate/severe malnutrition is evident.…”
mentioning
confidence: 93%
“…It did not go unnoticed that Ishizu et al 2 reported a higher prevalence of moderate/severe malnutrition regardless of index used in patients who are frail in comparison with patients who are not frail (statistically significant differences) as measured by the Clinical Frailty Scale. Looking closely at their Table 2 and the intersection between GNRI and Clinical Frailty Scale reported by Ishizu et al, 2 the overlap between frailty and moderate/severe malnutrition is evident. According to GNRI, 58% of all patients who were moderately/severely malnourished were found to be frail, and 70.6% of all patients who were frail were found to be malnourished.…”
mentioning
confidence: 93%
See 3 more Smart Citations